PROFESSIONAL KNOWLEDGE OF THE PSYCHOLOGIST. A CASE STUDY - Andrea M. Rodríguez; Margarita C. Ortiz (Revista del Instituto de Investigaciones en Educación, 2018)
The Professional Teaching Knowledge (CPD) is a complex process that requires reflexive processes to face the teaching and learning problems faced by the Psychologists and Graduates in Psychology of the Bachelor of Psychology of a university in northeastern Argentina. Numerous studies conclude that the teaching of psychology in this area generally assumes the traditional modality based on the didactic model of transmission. With the objective of promoting processes of change and innovation in pedagogical and institutional practices, the CPD is investigated, focusing on one of the tasks of the university teacher: teaching. To do this, we interview a sample of beginner and experienced teachers - from one of the venues of the career - classified as cases of "good teaching practices", by their students, in a survey. The interviewees denote personal and professional traits such as “knowing the subject and knowing how to teach it” that we synthesize in the following indicators: student achievements, their satisfaction with the teaching provided and passion for teaching.